CORRUPTION CRIMES PROJECT OF THE NATIONAL SPORTS SCHOOL AND TRAINING CENTER AT THE MINISTRY OF YOUTH AND SPORTS (Studi Putusan Nomor 2427K/Pid.Sus/2014 ) - Suparmin, Entol; Amsori (IBLAM LAW REVIEW, 2021)
Corruption, eradicating criminal acts of corruption, Decision No. 2427K / Pid.Sus / 2014, formulation: Is the imposition of criminal sanctions on corruption in the Ministry of Youth and Sports projects the same as the imposition of criminal acts of corruption in general, What is the basis for legal considerations for judges in imposing corruption crimes with Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption, the normative method is carried out on theoretical matters. Knowing whether the imposition of criminal sanctions on corruption is the same as the imposition of criminal acts of corruption in general. know what is the basis for legal considerations for judges in imposing crimes on perpetrators of Corruption Crime, the legal basis for adjudicating cases. The conclusion of the Judge's consideration, the imposition of additional criminal sanctions to compensate the state losses imposed on the defendant was imprisoned for 4 years and a fine, Article 2 paragraph (1) in conjunction with Article 18 of Law No. 31 of 1999 as amended by Law No. 20 of 2001 concerning the Eradication of Corruption in conjunction with Article 55 paragraph (1) 1 in conjunction with Article 65 paragraph (1) of the Criminal Code. Suggestions need evaluation In handling corruption crimes by implementing a synergy pattern between Indonesian National Police Investigators, Public Prosecutors , Prosecutor's Office, Corruption Eradication Commission.